Biomaterial Geotextile Berbahan Biomassa untuk Meningkatkan Produktivitas Pertanian di Desa Sidorejo Kabupaten Bojonegoro - Nikmatin, Siti; Husin, Abd Djamil; Mulyanto, Budi; Adiati, Rima Fitria (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to develop sustainable geotextiles made from local biomass. It involves training farmers in their production as an effort to reduce plastic use, improve soil health, and increase yields of papaya and chili crops. This community service implementation uses a participatory approach targeting farmers who are members of the